Correlation of Parenting Patterns with Development of Toddlers Aged 3 to 5 Years - Nindia Sefi Utami; Maya Safitri; Pramesti Dewi (Poltekkes Kemenkes Aceh, 2025)
Background: The development of children aged 3-5 years is a golden age that is greatly influenced by parenting patterns. Through the right parenting patterns can support the development of motoric, cognitive, social, and language of children. However, if not appropriate, it can inhibit child development and increase the risk of developmental delays. Purpose: To determine the relationship between parenting patterns and the development of toddlers aged 3-5 years in Samudra Kulon Village, Gumelar District, Banyumas Regency Methods: This study uses quantitative research with correlational methods through a cross-sectional approach. The research location is at Posyandu, Samudra Kulon Village, Gumelar District, Banyumas Regency with a sample of 62 parents and toddlers aged 3-5 years taken using Purposive Sampling. Data collection was carried out using the Developmental Pre-Screening Questionnaire (KPSP) consisting of 9-10 questions and the Parenting Styles and Dimensions Questionnaire - Short Version (PSDQ) consisting of 32 questions. Data analysis used the Spearman rank test. Results: Spearman rank correlation analysis shows a p-value ≤ 0.05, which means that there is a relationship between parenting patterns and the development of toddlers aged 3-5 years with a correlation coefficient value of 0.877 (the relationship between the two variables is very strong). Conclusion: There is a positive correlation between parenting patterns and the development of toddlers aged 3-5 years. The better the parenting patterns applied by parents, the more optimal the development of the child.